Vedolizumab as first-line biological therapy in elderly patients and those with contraindications for anti-TNF therapy: a real-world, nationwide cohort of patients with inflammatory bowel diseases. (2nd September 2021) - Attauabi, Mohamed; Höglund, Camilla; Fassov, Janne; Pedersen, Kenneth Bo; Hansen, Heidi Bansholm; Wildt, Signe; Jensen, Michael Dam; Neumann, Anders; Lind, Cecilie; Jacobsen, Henrik Albaek; Popa, Ana-Maria; Kjeldsen, Jens; et al.
Abstract: Background: Data from real-life populations about vedolizumab as first-line biological therapy for ulcerative colitis (UC) and Crohn's disease (CD) are emerging. Objective: To investigate the efficacy and safety of vedolizumab in bio-naïve patients with UC and CD. Methods: A Danish nationwide cohort study was conducted between November 2014 and November 2019. Primary outcomes were clinical remission, steroid-free clinical remission, and sustained clinical remission from weeks 14 through 52. Results: The study included 56 patients (UC:31, CD:25) who initiated treatment with vedolizumab mainly because of contraindications to anti-TNFs, of whom 54.8 and 24.0%, respectively received systemic steroids at the initiation. Rates of clinical remission at weeks 6, 14, and 52 were 32.0, 48.0, and 40.0%, respectively, in UC, and 36.8, 36.8, and 47.4% in CD. Steroid-free clinical remission at week 52 was achieved among 36.0 and 47.4% of UC and CD patients, while sustained clinical remission was achieved in 32.0 and 36.8%. Lack of remission was associated with being female (68.8 vs. 11.1%, p = .01) in UC and non‐structuring, non‐penetrating behavior in CD (90.0 vs. 44.4%, p = .03); however, this was not confirmed in multivariate analysis. Discontinuation due to primary non-response occurred in 20.0 and 5.3% of UC and CD patients, respectively, while rates of secondary loss of response were 12.0 and 5.3% after 52 weeks of follow-up. Vedolizumab was well-tolerated as only one UC patient experienced a serious adverse event. Conclusion: Vedolizumab is effective in the achievement of short-term, long-term, and steroid-free clinical remission in bio-naïve UC and CD patients.